Method comparison of beta‐hydroxybutyrate point‐of‐care testing to serum in healthy children. Issue 1 (22nd August 2021) - Parmar, Komalben; Mosha, Maua; Weinstein, David A.; Riba‐Wolman, Rebecca
Abstract: Ketone production is a physiological phenomenon that occurs to avoid irreversible neurological damage from hypoglycemia, thereby serving as a marker of metabolic stress. The primary ketone body, beta‐hydroxybutyrate (BHB), guides the diagnostic evaluation and management of many hypoglycemic disorders. Serum and point‐of‐care (POC) BHB values were not been compared in children without diabetes or metabolic disorders. We aim at comparing the serum and point‐of‐care BHB values in healthy children after an overnight fast. Eligible participants were ≤18 years of age prospectively recruited from elective procedures through our surgery centers. Exclusion criteria included a history of diabetes, hypopituitarism, adrenal, metabolic or inflammatory disorders, dietary restrictions, trauma, or use of medications that might affect blood glucose. The main outcome measure was comparing serum and POC BHB levels after a period of fasting. Data from 94 participants (mean age 8.29 ± 5.68 years, 54.3% male, 45.7% female, BMI mean 19.28 ± 5.25 kg/m 2 ) were analyzed. There was a strong correlation between serum BHB (mean 0.25 ± 0.23 mmol/L) and POC BHB (mean 0.18 ± 0.20 mmol/L) ( r s  = 0.803, p  < 0.0001). The majority (96.81%) of values for serum BHB compared with POC BHB fell within 0.1 ± 0.1 mmol/L. The average of difference between serum and POC BHB (the bias) was 0.064 mmol/L (95% CI 0.047–0.081), and percentage error was 3.19%. Point‐of‐care BHB is accurate and comparable to serum BHB levels in our cohort of children after an overnight fast. Synopsis: Point‐of‐care BHB agrees with serum values in healthy children.